Impacto das cinzas de queimadas no ambiente aquático e na comunidade fitoplanctônica - Jesus, Gabriel Sampaio de (2023)
Among the main threats to biodiversity are anthropic fires, a joint event, especially during the dry period. However, studies on the indirect effects of fires on aquatic ecosystems are scarce. In this study, we investigated how water quality and phytoplankton community structure might be affected by ash from fires in the Brazilian Cerrado. We used a microcosm experiment to simulate the aquatic environment with different scenarios of ash concentrations, and we evaluated over time the abiotic conditions, composition, richness, and phytoplankton density. We detected an increase in total phosphorus ammoniacal nitrogen concentrations after ash insertion. Regarding the phytoplankton community, we identified changes in composition as a function of time, and we did not recognize changes in richness and density in response to treatment. Our results indicate that ash from fires in the terrestrial environment can affect water quality and the species composition of aquatic communities. However, we suggest longer-duration experiments to evaluate the phytoplankton community's delayed responses.